2016
DOI: 10.1186/s12943-016-0539-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of programed cell death-1 (PD-1) and PD-ligand 1 (PD-L1) expression in cancer cells and tumor infiltrating lymphocytes in colorectal cancer

Abstract: BackgroundColorectal cancer (CRC) is 3rd most commonly diagnosed cancer in males and the second in females. PD-1/PD-L1 axis, as an immune checkpoint, is up-regulated in many tumors and their microenvironment. However, the prognostic value of PD-1/PD-L1 in CRC remains unclear.MethodsThe Cancer Genome Atlas (TCGA) database (N = 356) and Fudan University Shanghai Cancer Center (FUSCC) cohort of patients (N = 276) were adopted to analyze the prognostic value of PD-L1 in colorectal tumor cells (TCs) and of PD-1 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
202
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(221 citation statements)
references
References 36 publications
15
202
4
Order By: Relevance
“…Whereas immune cell-specific PD-L1 expression was found to be an independent prognostic factor, tumour cell-specific PD-L1 expression was not associated with survival neither in the full cohort nor in subgroup analysis according to PTL, supporting previous reports in CRC 16 , 17 , 19 , 22 and other cancers. 32-34 Nonetheless, an abundance of studies have reported high PD-L1 expression to be associated with an impaired prognosis due to induction of immune evasion, 6 , 7 , 35 being the rationale for PD-1/PD-L1 blockade.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Whereas immune cell-specific PD-L1 expression was found to be an independent prognostic factor, tumour cell-specific PD-L1 expression was not associated with survival neither in the full cohort nor in subgroup analysis according to PTL, supporting previous reports in CRC 16 , 17 , 19 , 22 and other cancers. 32-34 Nonetheless, an abundance of studies have reported high PD-L1 expression to be associated with an impaired prognosis due to induction of immune evasion, 6 , 7 , 35 being the rationale for PD-1/PD-L1 blockade.…”
Section: Discussionsupporting
confidence: 80%
“…17 , 19 , 22 Moreover, in subsite analysis according to PTL, PD-L1 expression was independently associated with a prolonged survival in patients with right-sided and left-sided colon cancers, but not in patients with rectal cancer. These findings further support previous evidence suggesting that proximal and distal CRC may represent different epidemiological, pathological, genetic, and clinical entities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…10,26 Unlike most tumors, in which PD-1 overexpression clearly correlates with impaired survival, PD-1 expressions seems to be paradoxically associated with improved outcome in primary CRC. 10,11 This is possibly based on specific features of the intestine immune system, which is constantly exposed to commensal microbiota. Furthermore, expression of PD-L1 in primary rectal cancer has been shown to be rare or even absent.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 and PD-L1 expressing tumor-infiltrating lymphocytes (TIL) at the primary tumor site lead to prolonged recurrence free and overall survival. 10,11 This unique finding in CRC has been controversially discussed in the literature and is explained by the gut specific microenvironment and particular features of the intestinal immune system.…”
Section: Introductionmentioning
confidence: 99%